Fog type classification using a modified Richardson number for Christchurch, New Zealand. (22nd June 2022) - Lin, Dongqi; Katurji, Marwan; Revell, Laura E.; Khan, Basit; Osborne, Neal; Soltanzadeh, Iman; Kremser, Stefanie
Abstract: Situated on a coastal plain between the Southern Alps and Banks Peninsula, Christchurch, New Zealand, experiences around 49 fog days every year. Given its complex topography, accurate fog forecasting is difficult at Christchurch International Airport (CHA). Climatological analysis of local fog events is an important first step to gain insight into the processes involved in the fog lifecycle. In this study, fog events were identified using 12 years of meteorological observations from an automatic weather station situated at CHA. A novel fog type classification method was developed using the modified Richardson number ( MRi ). The MRi fog type classification method assesses the local dynamic stability of a 1.25 m shallow layer of near‐surface air. Here, the MRi is used as a quantitative index to classify advection fog, advection–radiation fog, and radiation fog. Vertical gradients of air temperature and wind speed were derived for prefog and fog periods, and a number of criteria were applied to the MRi for the fog type classification. The fog type classification results were examined in correspondence with the derived fog intensity, duration, diurnal and seasonal variability of frequency of occurrences, and synoptic and local wind flows. In agreement with other fog studies across the world, fog occurs most frequently during local winter and spring. Radiation fog is the predominant type of fog identified at CHA, and its formation and development usually coincide with the local drainage northwesterlies. This study is the first to use long‐term observational data to investigate the fog climatology and typology at CHA in detail. The fog climatological characteristics presented in this study will serve as the basis of future fog studies in Christchurch. The presented MRi fog type classification method can potentially be used in fog characteristic studies worldwide. Abstract : The modified Richardson number ( MRi ) has been used to classify fog types for Christchurch, New Zealand. The MRi is a quantitative index that provides an evaluation of the dynamic stability of a shallow layer of near‐surface air. The classification results are verified by the derived climatological characteristics of each fog type and provide an insight of the processes involved in fog development.